2022
DOI: 10.1097/fbp.0000000000000702
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde dehydrogenase 2–associated changes in pharmacokinetics, locomotor function and peripheral glutamic acid and gamma-aminobutyric acid levels during acute alcohol intoxication in male mice

Abstract: The insufficiency of human aldehyde dehydrogenase 2 (ALDH2) has been consistently associated with high blood acetaldehyde levels and impaired locomotor function during acute alcohol intoxication. The ALDH2-associated change in peripheral glutamic acid (Glu) and gamma-aminobutyric acid (GABA) levels and its correlation with pharmacokinetics and psychomotor function remain unclear. In this study, ALDH2*2 mice were used to build an acute alcohol intoxication model after intraperitoneal administration. The blood e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Accordingly, ALDH2*2 mice are an ideal model for the research of human diseases associated with ALDH2 deficiency ( Chen et al, 2014 ). Our previous study also observed the accumulation of acetaldehyde in ALDH2*2 mice after acute alcohol administration, which confirmed the insufficiency of ALDH2 activity ( Li et al, 2022 ).…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…Accordingly, ALDH2*2 mice are an ideal model for the research of human diseases associated with ALDH2 deficiency ( Chen et al, 2014 ). Our previous study also observed the accumulation of acetaldehyde in ALDH2*2 mice after acute alcohol administration, which confirmed the insufficiency of ALDH2 activity ( Li et al, 2022 ).…”
Section: Introductionsupporting
confidence: 76%
“…Based on anesthesia, approximately 100 μL of the blood sample was collected from the mouse orbital venous sinus and was placed in a heparin sodium anticoagulated EP tube. After 50 μL of blood was prepared by using the optimized PCA method, the ethanol and acetaldehyde concentration in whole blood was determined by Headspace Gas Chromatography coupled with flame ionization ( Xiong et al, 2014 ; Li et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…27 Studies have shown that the Glu/GABA nervous system is closely associated with depression, suicide, and drug addiction. 28 Changes in proteins that regulate Glu transmission are critical for relapse. 29 Animal studies have found that addictive drug abuse leads to increased levels of Glu in the prefrontal cortex, and restraint stress-induced addiction relapse can lead to increased levels of Glu in the prefrontal cortex and striatum, while addictive drugs also have an inhibitory effect on the GABA system.…”
Section: Discussionmentioning
confidence: 99%